Pedagogical approaches in language teaching: How can teachers build on their students’ plurilingualism? - Pesková, Renata Emilsson (Milli Mála, 2022)
Plurilingualism affects students’ education, school achievement, and wellbeing. This article describes the instructional approaches that compulsory schoolteachers and heritage language (HL) teachers used to draw on the linguistic repertoires of their students. The participants of the study were five class teachers and five HL teachers who all worked in the Greater Reykjavík Area. The research was qualitative, and a thematic analysis was used to analyze semi-structured interviews. The findings showed that the class teachers were generally interested in their students’ HL languages and HL school attendance, while their pedagogies did not respond to students’ plurilingualism. Some HL teachers had knowledge of Icelandic and the Icelandic school system, yet their goal was their students’ development of HL, and they applied monolingual instructional strategies. One class teacher and one HL teacher built systematically on their students’ plurilingualism in their teaching. This research raises questions about the previously held views that it is primarily the roleof the school to teach students Icelandic, and the responsibility of parents to maintain and develop HL languages. It is in the interest of plurilingual students that their teachers assume holistic, empowering, plurilingual approaches to teaching. This research suggests that educators need access to relevant professional development, they need to initiate respectful collaboration with immigrant parents, and in a broader sense, view plurilingualism as the norm and recognize the equal value of all languages in schools and societies.Keywords: Plurilingual students, linguistic repertoire, plurilingual pedagogical approaches, linguistic identity, multiple case study Fjöltyngi hefur áhrif á nám, námsárangur og vellíðan. Greinin lýsir kennsluaðferðum og nálgunum bekkjarkennara og móðurmálskennara og þá sérstaklega hvernig þeir hafa nýtt sér tungumálaforða nemenda í skólastarfinu. Þátttakendur voru fimm bekkjarkennarar á miðstigi grunnskóla (5.–7. bekkur) og fimm ...